Digestion of protein and toxic gluten peptides in wheat bread, pasta and cereal and the effect of a supplemental enzyme mix - Daniela Freitas; Laura G. Gómez-Mascaraque; André Brodkorb (Frontiers in Nutrition, 2022)
There has been an increasing interest in the relationship between wheat digestibility and potential toxicity to the host. However, there is a lack of understanding about temporal profile of digestion of wheat proteins from different food matrices under physiologically relevant conditions. In this study, digestion of three wheat-based foods (bread, pasta and cereal) was conducted based on the INFOGEST semi-dynamic protocol in the absence and presence of a commercial supplemental enzyme preparation (a Glutalytic® based supplement, which will be marketed as Elevase®). Protein hydrolysis (OPA- ortho-phthalaldehyde - assay), molecular weight distribution (SEC-HPLC) and potential toxicity (R5 antibody-based competitive ELISA), were assessed. Our results demonstrated that under normal conditions, the complexity of the food influenced the temporal profile of protein hydrolysis and gluten breakdown throughout simulated gastric and intestinal digestion. However, treatment with the enzyme supplement significantly and acutely increased protein hydrolysis and gluten degradation in the gastric stage, and this enhanced digestion was maintained into the intestinal environment. These findings highlight the limitations of temporal gastric proteolysis and gluten degradation under normal conditions to different food types. They also show that supplemental enzyme mixes can effectively accelerate the breakdown of protein and hydrolysis of toxic gliadin fractions from the early stages of gastric digestion, thereby reducing intestinal exposure and potentially limiting the sensitization of the host.